THE AUTHORITY OF POLICE INVESTIGATORS IN ERADICATION OF CRIMINAL ACTS OF CORRUPTION - Cahyo Dati Widodo; Syafiuddin A rahim; Abdi Negara (Universitas 17 Agustus 1945 Semarang, 2021)
Law Number 19 of 2019 concerning the Law on Corruption Eradication Commission which is a renewal of Law Number 31 of 1999 as amended by Law Law No. 20 of 2001 concerning Eradication of Corruption, instead of Law number 3 of 1971. The enactment of this law is expected to accelerate the growth of people’s welfare, responding to the evil nature contained in corruption. The problem in this study is how is the authority of police investigators in eradicating criminal acts of corruption after the issuance of Law Number 19 of 2019 concerning Law on Corruption Eradication Commission and what obstacles faced by investigators related to the authority of police investigators in eradicating criminal acts of corruption after the issuance of Law on Corruption Law Number 19 of 2019 concerning Law on Corruption Eradication Commission. The method in this study uses descriptive qualitative research methods with a normative juridical approach. The results of this study are : (1) The authority of police investigators is to carry out investigations. Investigation activities are a follow-up to investigations that have found the construction of corruption crimes that have occurred to some extent. The law gives special rights or privileges to investigators to carry out investigative functions such as summoning, examining, arresting, detaining, confiscating, and determining suspects. (2) The obstacles faced concerning the authority of police investigators are a) The number of members of criminal investigators is limited. b) Information received regarding criminal acts of corruption is still unclear and in detail. c) Operating costs that have not been met. d) Lack of public legal awareness. The solution to the obstacles faced is by a) Gradually increasing the number of criminal investigators. b) Speed up all access to information related to criminal acts of corruption. c) The government needs to increase the operational cost budget item. d) It is necessary to hold outreach to the community either directly or through electronic media or social media.